Association of immune cell recruitment and BPD development - Heydarian, M.; Schulz, C.; Stöger, T.; Hilgendorff, A. (Molecular and Cellular Pediatrics, 2022)
In the neonatal lung, exposure to both prenatal and early postnatal risk factors converge into the development of injury and ultimately chronic disease, also known as bronchopulmonary dysplasia (BPD). The focus of many studies has been the characteristic inflammatory responses provoked by these exposures. Here, we review the relationship between immaturity and prenatal conditions, as well as postnatal exposure to mechanical ventilation and oxygen toxicity, with the imbalance of pro- and anti-inflammatory regulatory networks. In these conditions, cytokine release, protease activity, and sustained presence of innate immune cells in the lung result in pathologic processes contributing to lung injury. We highlight the recruitment and function of myeloid innate immune cells, in particular, neutrophils and monocyte/macrophages in the BPD lung in human patients and animal models. We also discuss dissimilarities between the infant and adult immune system as a basis for the development of novel therapeutic strategies.